Autistic Christians and their experiences of faith, worship, and community in Evangelical churches in the UK - Peach, Elizabeth L. (Practical theology, 2025)
This study explores what autistic Christians who attend evangelical churches in the UK find both valuable and challenging about how they experience faith, worship, and community within these contexts. The aim was to enable autistic people’s voices to be heard, and to explore the interaction between autistic experience and evangelical church environments. In-depth semi-structured interviews with seven autistic Christians from evangelical churches were conducted, and the data analysed by thematic analysis. The participants expressed highly positive views of God, and demonstrated that they deeply value their faith and church involvement. However, the significant personal costs for them in participating in these communities were also evident. Although which aspects of church life were difficult or enjoyable varied greatly among the participants, there were common experiences of exhaustion, overwhelm, and a sense of failure. The significance of the presence of autistic people within the body of Christ, and what it means for autistic people to live as disciples of Christ are also considered.